Audio and Video Communication Software Design Based on SIP - Shanshan Peng (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper makes a design which implements the audio and video communication based on SIP over the Win2K platform. The oSIP and eXosip were used to exchange the Signals, and the jrtp was for packing the audio and video data. In the end, the multithreading was adopted to make the software perform well.